2016
DOI: 10.1039/c5cc08464d
|View full text |Cite
|
Sign up to set email alerts
|

Chirality induction using circularly polarized light into a branched oligofluorene derivative in the presence of an achiral aid molecule

Abstract: Chirality induction to a uniform, star-shaped fluorene oligomer with a central truxene moiety (T3) was achieved using circularly polarised light in the presence of achiral fluorene or phenanthrene. Induction to T3 alone was difficult, suggesting that close chain packing realised through interactions of T3 with small molecules plays a role in chirality induciton.Circularly polarised light (CPL) was proposed to be a source of chirality for the synthesis of asymmetric organic molecules for the first time in 1874,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 26 publications
(6 reference statements)
1
38
0
Order By: Relevance
“…Conjugate polymers are continuously raising widespread attention owing to their versatile features spanning applications from organic electronics, photovoltaic devices towards nanomedicine 1 . Their flexible uses stem from the typical molecular organization, which confers them a specific chemical scaffold 2–11 . For instance, amorphous arrangements have been so far related to spurious cis ‐defects arising during chemical synthesis 12 or owing to their backbone flexibility 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Conjugate polymers are continuously raising widespread attention owing to their versatile features spanning applications from organic electronics, photovoltaic devices towards nanomedicine 1 . Their flexible uses stem from the typical molecular organization, which confers them a specific chemical scaffold 2–11 . For instance, amorphous arrangements have been so far related to spurious cis ‐defects arising during chemical synthesis 12 or owing to their backbone flexibility 13 .…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32] However, the mixing of the dopants affects the lm structure and interferes with the properties of the organic semiconductors. The application of chiral stimuli to the materials, such as irradiation with circularly polarized light, can also induce enantiomorphic structures, [33][34][35] but the enantiomorphic effects are generally weak. To our knowledge, chiral induction during crystallization has not been reported for thin-lm organic semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…Chemists have successfully realized the helical chirality switching by means of external stimuli, such as solvent, temperature, light irradiation, pH and so on. [21][22][23][24][25][26][27][28][29][30][31] In particular, intrinsic chirality exists in many organic solvents (e.g., limonene), and it tends to influence the solute conformation, then results in complete helical chirality inversion. Gin and Moore demonstrated that [This article is part of the Special Issue: Proceedings of 28th International Symposium on Molecular Chirality, Heidelberg 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, supramolecular helical handedness of chiral materials is not invariable, actually, they display conformational transformations under certain treatments. Chemists have successfully realized the helical chirality switching by means of external stimuli, such as solvent, temperature, light irradiation, pH and so on . In particular, intrinsic chirality exists in many organic solvents (e.g., limonene), and it tends to influence the solute conformation, then results in complete helical chirality inversion.…”
Section: Introductionmentioning
confidence: 99%